Disentangle Kinetic From Equilibrium Fractionation Using Primary (δ17O, δ18O, δD) and Secondary (Δ17O, dex) Stable Isotope Parameters on Samples From the Swiss Precipitation Network - Leuenberger, Markus C.; Ranjan, Shyam (Frontiers in Earth Science, 2021)
Since 1971 water isotope measurements are being conducted by the Climate and Environmental Physics Division at the University of Bern on precipitation, river- and groundwater collected at several places within Switzerland. The water samples were stored in glass flasks for later analyses with improved instrumentation. Conventional isotope ratio measurements on precipitated water from all stations of the network are well correlated as expected. However, 17O as well as dex is anticorrelated to these isotope ratio. The combination of these parameters allow to investigate dependencies on temperature, turbulence factor, and humidity of these values as well as to look into the importance and relative contributions of kinetic to equilibrium fractionations. We used published temperature dependent fractionation factors in combination with a Rayleigh model to investigate the importance of the meteorological parameters on the isotope ratios. A direct comparison of measured and modelled isotope ratios for primary (17O, (18O and (D) as well as secondary isotope parameters (17O and dex) is shown.